Intermediate and long‐term outcomes of fibroadenoma excision in adolescent and young adult patients. Issue 1 (16th November 2018) - Javed, Asma; Jenkins, Sarah M.; Labow, Brian; Boughey, Judy C.; Lemaine, Valerie; Neal, Lonzetta; Shah, Sejal S.; Pruthi, Sandhya
Abstract: Fibroadenomas are benign breast masses that often occur in adolescence and young adulthood. Primary management options include observation or surgical excision, but little is known about long‐term outcomes after fibroadenoma excision in adolescents. In the present study, we reviewed the medical records of females aged 13‐35 years who underwent fibroadenoma excision at our institution from 1986 through 2010. Patients were included if they had excision of at least 1 fibroadenoma (confirmed by histopathology) smaller than 5 cm in maximal diameter. We collected information pertaining to clinical presentation, management, and outcomes. In addition, an investigator‐designed long‐term outcome survey was sent to 138 eligible participants to assess patient satisfaction, as well as the recurrence of fibroadenoma, and the need or desire for further surgical intervention. Most patients (126 of 138) underwent 1 operation for fibroadenoma excision. Three women underwent immediate breast reconstruction at fibroadenoma excision. Fifty‐seven patients completed the investigator‐designed survey (response rate, 41.3%) with a median follow‐up time of 13.5 (range, 2.0‐26.7) years. Nine of 55 patients (16.4%) reported postoperative breast asymmetry and the desire to pursue reconstructive surgery. Three survey responders reported breast pain. Fourteen of 56 women (25.0%) reported the diagnosis of 1 or more additional fibroadenomas after the initial excision; another 7 reported recurrence of the mass at the site of excision. Most survey participants were satisfied with the aesthetic outcome of their fibroadenoma excision; however, a small proportion believed that they would benefit from reconstructive breast surgery. The recurrence and development of additional fibroadenomas should be addressed by providers during counseling for treatment options and postoperative follow‐up.